2013
DOI: 10.1007/s10096-013-1863-3
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus bovis/Streptococcus equinus complex fecal carriage, colorectal carcinoma, and infective endocarditis: a new appraisal of a complex connection

Abstract: The proportion of group D streptococcal infective endocarditis (IE) (predominantly due to Streptococcus gallolyticus) and the incidence of colorectal cancer are higher in France than in most European countries. We assumed that this could be explained by a high group D streptococci (GDS) fecal carriage rate. The aims of this study were to re-assess the GDS fecal carriage rate in France and its relationship with colorectal cancer. Consecutive adult subjects who were to undergo a complete colonoscopy were invited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
1
22
2
Order By: Relevance
“…pasteurianus, n ϭ 2; and S. gallolyticus subsp. gallolyticus, n ϭ 1 (14). Our results were in agreement with theirs, with S. infantarius subsp.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…pasteurianus, n ϭ 2; and S. gallolyticus subsp. gallolyticus, n ϭ 1 (14). Our results were in agreement with theirs, with S. infantarius subsp.…”
supporting
confidence: 93%
“…This fecal carriage rate is higher than those observed in prior studies (3,12,13). Notably, a recently published study (14) showed that the fecal carriage rate of SBEC subspecies was 4.6% among adult subjects with tumorous lesions, nontumorous lesions, and normal colonoscopy results. Those authors used a biomolecular technique and identified SBEC subspecies in the feces of 12 of 259 subjects, with the following distribution: S. lutetiensis (S. infantarius subsp.…”
contrasting
confidence: 56%
“…31,32 Consequently in settings with high rates of CRN an increased rates of Sb bacteraemia might be expected, which is the case of France presenting high incidence of CRN. 33 We do not know the incidence of CRN in our areas, but we know the incidence of mortality due to CRN, which was significantly higher in the cattle area than in the other two areas (Fig. 2), 34,35 Interestingly, some studies have shown an association of long-term consumption of red meat with increased risk of CRN, 36 and although the causality for this association is unknown it should be noted down that Sb could be isolated from meat.…”
Section: Discussionmentioning
confidence: 99%
“…SBSEC colonize the GI-tract of humans where they are commensal and potentially opportunistic pathogenic bacteria. The faecal carriage rate of SBSEC is estimated around 23.8% in neonates and 5% in adults (Noble, 1978) with more precise recent estimations for SBSEC around 4.6% comprising S. lutetiensis as predominant member (Chirouze et al, 2013). However, in countries where live SBSEC members are consumed in large amounts via fermented food (Jans et al, 2013b;Tsakalidou et al, 1998), the faecal load might be higher.…”
Section: Global Epidemiology Of Sbsec In Humans and Their Role In Dismentioning
confidence: 99%